Clinical and microbiological features of ceftolozane/tazobactam-resistant Pseudomonas aeruginosa isolates in a university hospital in central Italy. (September 2022) - Morroni, Gianluca; Brescini, Lucia; Antonelli, Alberto; Di Pilato, Vincenzo; Castelletti, Sefora; Brenciani, Andrea; D'Achille, Gloria; Mingoia, Marina; Giovanetti, Eleonora; Fioriti, Simona; Masucci, Annamaria; Giani, Tommaso; et al.
Highlights: Ceftolozane/tazobactam (C/T) is a new cephalosporin β-lactamase inhibitor combination. Pseudomonas aeruginosa harbored various resistance mechanisms to C/T. Metallo β-lactamase and extended spectrum β-lactamase (ESBL) are the main resistance mechanisms. Epidemiology and resistance mechanisms to C/T varied in P. aeruginosa strains. ABSTRACT: Objectives: Ceftolozane/tazobactam (C/T) is a novel cephalosporin and β-lactamase inhibitor combination with great activity against Pseudomonas aeruginosa . To assess P. aeruginosa susceptibility to C/T, a surveillance study was conducted from October 2018 to March 2019 at the University Hospital 'Ospedali Riuniti' in Ancona, Italy. Methods: Minimum inhibitory concentrations (MICs) to C/T were determined by Etest strip. Resistant isolates were characterized by phenotypic (broth microdilution antimicrobial susceptibility testing and modified Carbapenem Inactivation Method [mCIM]) and genotypic (Polymerase Chain Reaction [PCR], Pulsed Field Gel Electrophoresis [PFGE], and whole-genome sequencing [WGS]) methods. Clinical variables of patients infected by C/T-resistant P. aeruginosa were collected from medical records. Results: Fifteen of 317 P. aeruginosa collected showed resistance to C/T (4.7%). Ten strains demonstrated carbapenemase activity by mCIM method, and PCR confirmed that eight strains harbored a blaVIM gene while the other two were positive for blaIMP . Additionally, three isolates carried acquired extended spectrum β-lactamase genes (two isolates carried blaPER and one carried blaGES ). Eight strains were strictly related by PFGE and WGS analysis confirmed that they belonged to sequence type (ST)111. The other STs found were ST175 (two isolates), ST235 (two isolates), ST70 (one isolate), ST621 (one isolate), and the new ST3354 (one isolate). Most patients had received previous antibiotic therapies, carried invasive devices, and experienced prolonged hospitalization. Conclusion: This study demonstrated the presence of C/T-resistant P. aeruginosa isolates in a regional hospital carrying a number of resistance mechanisms acquired by different high-risk clones.